Laser-based measurements for time and frequency domain applications : a handbook - Maddaloni, Pasquale. (Series in optics and optoelectronics (CRC Press), 2013)
"Providing a self-contained introductory review of modern laser-based time and frequency measurement techniques, this text represents an interdisciplinary look at the recent developments and future directions of optical frequency meteorology, as well as a range of meteorological disciplines. Suitable for graduate students and practicing physicists and engineers, it discusses the most advanced laser-based spectroscopic measurement techniques, including UV, j1W, visible frequency, and IR laser. The authors, leading optical meteorologists, also cover advanced spectroscopic techniques, experimental quantum optics, and quantum information"--